High-power piezoelectric behavior of acceptor-doped 〈001〉 and 〈111〉 textured piezoelectric ceramics. Issue 6 (25th January 2023) - Leng, Haoyang; Yan, Yongke; Li, Xiaotian; Karan, Sumanta Kumar; Fanton, Mark; Priya, Shashank
Abstract : The high-power piezoelectric properties of MnO2 -doped 〈001〉 and 〈111〉 textured 0.24PIN–0.42PMN–0.34PT ceramics are compared to understand the orientation dependence. Abstract : Piezoelectric ceramics with high piezoelectric co-efficient, d 33, and mechanical quality factor, Q m, are required in high-power applications. 〈001〉 and 〈111〉 textured Pb(In1/2 Nb1/2 )O3 –Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 ceramics were fabricated using templated grain growth method and their high-power electromechanical properties were characterized. It is shown that 〈001〉 textured ceramics possess higher d 33 compared to random and 〈111〉 textured counterparts, while the Q m is strongly enhanced in 〈111〉 textured ceramics due to less favored polarization rotation. MnO2 doping is shown to further improve the Q m values for both 〈001〉 and 〈111〉 textured ceramics because of the restricted polarization switching induced by the defect dipole. Doped 〈001〉 textured ceramics can exhibit the high d 33 and moderate Q m ( d 33 = 725 pC N −1, Q m = 716) in comparison with 〈111〉 textured ceramics exhibiting low d 33 and high Q m ( d 33 = 350 pC N −1, Q m = 1495). Owing to the combinatory soft and hard piezoelectric properties, the doped 〈001〉 textured ceramics exhibit 1.5× higher vibration velocity (∼0.90 m s −1 ) in comparison with commercial hard PZTs. Interestingly, a slightly higher vibration velocity (∼0.94 m s −1 ) can be obtained in doped 〈111〉 textured ceramics, which is mainly attributed to the high Q m and low elastic compliance s 11 . These results demonstrate the promise of textured piezoelectric ceramics for high-power applications.